Efecto de la edad relativa en el proceso de selección de jugadores para las selecciones autonómicas de balonmano - Gomez Lopez, M.; Sanchez, S. A.; Ruiz Sanchez, V. (Revista Ciencia del Deporte, 2017)
This study aimed to analyze the effect of age on adolescent handball players of the regional selection teams. To do this, data of sex and date of birth of 84 youth players from different regional selection teams in the 2015-2016 season were analyzed, performing comparisons and differences being studied by ?2 and Z tests and the Bonferroni method. The analysis of results by quarter and half of birth revealed no statistically significant differences in gender and category. It seems to confirm that there is not relative age effect in the analyzed Teams. Whereupon, seems to confirm that in handball base, all young people participate, regardless of the degree of maturity submit.